2009
DOI: 10.1080/15368370902724872
|View full text |Cite
|
Sign up to set email alerts
|

Metal, EMF, and Brain Energy Metabolism

Abstract: Some implications of cooperative potential of metal ions and electromagnetic fields' radiation (EMF) in carcinogenic processes are discussed. It is known that these factors, chemical and physical individually have connections with processes of oxidative stress. Special attention was paid to possible manifestation within the brain. Therefore, the entry of a few potentially neurotoxic metals into the brain is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Because of the lack of a reliable animal model that would ensure defined exposure parameters, it is difficult to directly compare experimental results and to draw definitive conclusions. On the other hand, the majority of existing results have shown that the increased exposure to electromagnetic radiation may lead to hazardous effects on the brain (Vojtísek et al 2009, Hao et al 2015, suggesting the need for further research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of a reliable animal model that would ensure defined exposure parameters, it is difficult to directly compare experimental results and to draw definitive conclusions. On the other hand, the majority of existing results have shown that the increased exposure to electromagnetic radiation may lead to hazardous effects on the brain (Vojtísek et al 2009, Hao et al 2015, suggesting the need for further research in this field.…”
Section: Introductionmentioning
confidence: 99%